Tanggung Jawab Indonesia dalam Penanganan Covid-19 melalui Vaksinasi ditinjau dari Perspektif Hukum Internasional - Muhammad Fardi Sofari (Faculty of Law, Universitas Airlangga, 2023)
Abstract This article aims to identify and analyze the regulations for handling Covid-19 according to international law and Indonesia's responsibilities in fulfilling the Covid-19 vaccination. This article is a normative-legal research that uses a combination of a statutory approach and a conceptual approach. The conclusion obtained is that the right to get vaccinated and the responsibility of the state in fulfilling vaccinations is carried out by the Indonesian government to protect its citizens from being infected with Covid-19 as a fulfillment of individual rights based on human rights according to international law by take into account the provisions in The Universal Declaration of Human Rights. (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). Keywords: international law; covid-19 vaccination; state responsibility. Abstrak Artikel ini bertujuan untuk mengetahui dan menganalisis peraturan penanganan Covid-19 menurut hukum internasional serta tanggung jawab Indonesia dalam pemenuhan vaksinasi Covid-19. Artikel ini merupakan penelitian hukum normatif yang menggunakan kombinasi antara pendekatan peraturan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Kesimpulan yang diperoleh adalah bahwa hak mendapatkan vaksinasi dan tanggung jawab negara dalam pemenuhan vaksinasi dilakukan oleh pemerintah Indonesia untuk melindungi warga negaranya agar tidak terjangkit Covid-19 sebagai pemenuhan hak individu berdasarkan hak asasi manusia menurut Hukum Internasional dengan memperhatikan ketentuan dalam The Universal Declaration of Human Rights (UDHR) dan International Covenant on Civil and Political Rights (ICCPR). Kata Kunci: hukum internasional; vaksinasi covid-19; tanggung jawab negara.